2008
DOI: 10.1167/iovs.07-1325
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Preserves the Dendritic Morphology of α and β Ganglion Cells in the Cat Retina after Optic Nerve Injury

Abstract: BDNF, in addition to promoting ganglion cell survival, plays an important role in preserving the somal and dendritic morphologies of the surviving ganglion cells, a necessary precursor to maintaining normal visual function. Ganglion cells, however, are not created equal with respect to their responses to nerve injury or to treatment of the eye with BDNF. Thus, development of effective treatment strategies for preserving ganglion cell function in optic nerve-related diseases mandates a clearer understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 56 publications
2
39
0
2
Order By: Relevance
“…[60][61][62] In mice, the effect of BDNF has been mainly analyzed in models of photoreceptor degeneration, 63-65 but its effect on RGC survival after optic nerve injury is unknown. We studied two mouse strains, a pigmented and an albino strain, and found that in both strains the response to IONT and BDNF or vehicle treatment was similar in terms of RGC survival and microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62] In mice, the effect of BDNF has been mainly analyzed in models of photoreceptor degeneration, 63-65 but its effect on RGC survival after optic nerve injury is unknown. We studied two mouse strains, a pigmented and an albino strain, and found that in both strains the response to IONT and BDNF or vehicle treatment was similar in terms of RGC survival and microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…20 Dendritic shrinkage after optic nerve crush has been documented histologically in cats. 21 Leung et al 22 studied the same YFP-expressing mouse strain after nerve crush with in vivo imaging of the same RGCs over time. They documented dendritic constriction in 68% of 125 RGCs studied in 12 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Weber et al 8,21,38 have individually identified RGCs electrically, then filled them with dye for postmortem study in cats and monkeys. This elegant approach has yielded important findings, but is limited by the number of neurons that can be injected per eye and by possible selectivity in which RGCs are more likely to be successfully penetrated.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in the feline retina demonstrated that a cells endowed with large somata and dendritic arbors undergo a significant decrease in dendritic field size after axotomy, while b cells with medium-sized somata and more compact dendritic trees are less affected (Weber and Harman, 2008). Recent work supporting the idea that the dendrites of distinct RGC subtypes are differentially affected depending on the onset, duration of injury, and arbor stratification (Della Santina et al, 2013;El-Danaf and Huberman, 2015;Feng et al, 2013;Morquette et al, 2014) will be described below.…”
Section: Morphological Diversity Of Rgc Dendrites: An Embarrassment Omentioning
confidence: 97%